Restrictions on religious practices in selected European countries during the COVID-19 pandemic: A legal-sociological study from Poland’s experiences - Skoczylas, Łukasz; Piątek, Wojciech; Olszanowski, Jan; Golędzinowski, Filip (Society Register, 2023)
The aim of this paper is to present legal restrictions related to religious ceremonies during the Covid-19 pandemic, which are not currently in force in Poland but are being applied in selected European countries. The study examines the possible extent of their acceptance by believers in Poland, a country with persistently high levels of religious observance. It transpires that negative evaluations prevail in the case of the following restrictions: advanced registration for participation in religious services, the possibility of only vaccinated persons participating in services, and singing being prohibited. On the other hand, a more positive view was taken of designating specific places that can be occupied in the place of worship, and the requirement for all attendees to wear a mask (including priests and leaders of religious practices). The research revealed a general tendency for those who participate more frequently in religious practices to view restrictions more negatively.